Questioning the Wet Space: A Comparative Analysis of Health and Hygiene in Modern Apartment Interiors in Turkey - Öztürk, Selim Sertel; Pasin, Burkay (Docomomo Journal, 2025)
While the modernist discourses of the 20th century pretended to solve all the problems of daily life through the acts of standardization, unification, and scientific progress, the modernist practice incorporates its advancements and conflicts within the same built environment. One such discourse is on domestic health and hygiene, which proposes to integrate various functions of bathing, cleaning, washing, and defecation within the so-called volume ‘wet space’, equipped with modern utilities. It is questionable how healthy and hygienic such a spatial model is compared to traditional domestic life, in which most of these functions have been segregated and/or performed according to cultural norms. This neglected problem has become evident with long-term lockdowns due to the COVID-19 pandemic, especially in apartment blocks where all inhabitants have to share a single wet space throughout the day. This paper questions whether the modernist discourses of health and hygiene function properly in modern domestic architecture and how the conflicts of wet space can be read. Accordingly, we concentrate on selected apartments in Turkey that were built between 1950 and 1970 and are still in use today: Ataköy Housing Estate, Phase I-II, and Yeşiltepe Blocks, developed and built by the Emlak Kredi Bank. Through scholars’ and architects’ discourses and practices on domestic hygiene derived from articles and architectural drawings in national archives, the paper provides a comparative analysis of wet spaces in these apartments in terms of their location within the spatial layout, the utilities and materials applied, as well as their privacy level. The analysis shows that the limitations of the wet space in these modern apartment interiors reveal the possible risks to domestic health and hygiene, particularly in times of pandemic.